Kidneys in SARS‐CoV‐2 era: A challenge of multiple faces. Issue 3 (1st March 2022) - Abdelsalam, Mostafa; Abd El Wahab, Ahmed M.; Nassar, Mohammed Kamal; Samaan, Emad; Eldeep, Ahmed; Abdalbary, Mohamed; Tawfik, Mona; Saleh, Marwa; Shemies, Rasha Samir; Sabry, Alaa
Abstract: Introduction: With the evolution of SARS‐CoV‐2 pandemic, it was believed to be a direct respiratory virus. But, its deleterious effects were observed on different body systems, including kidneys. Aim of Work: In this review, we tried as much as we can to summarize what has been discussed in the literature about the relation between SARS‐CoV‐2 infection and kidneys since December, 2019. Methods: Each part of the review was assigned to one or two authors to search for relevant articles in three databases (Pubmed, Scopus, and Google scholar) and collected data were summarized and revised by two independent researchers. Conclusion: The complexity of COVID‐19 pandemic and kidney could be attributed to the direct effect of SARS‐CoV‐2 infection on the kidneys, different clinical presentation, difficulties confronting dialysis patients, restrictions of the organ transplant programs, poor outcomes and bad prognosis in patients with known history of kidney diseases who got infected with SARS‐CoV‐2.